Description of a new species of Pseudopaludicola Miranda-Ribeiro, 1926 from the state of São Paulo, Southeastern Brazil (Anura, Leiuperidae) - Toledo, Luis Felipe; Siqueira, Sergio; Duarte, Thiago C.; Veiga-Menoncello, Ana Cristina P.; Recco-Pimentel, Shirlei M.; Haddad, Celio Fernando Baptista [UNESP] (Magnolia Press, 2010)
We describe here a new species of Pseudopaludicola (P. murundu sp. nov.) that is found in the central portion of the state of São Paulo, Brazil. This new species is related to P. saltica, from which it distinguishes by the presence of a single, dark, and subgular vocal sac with dark longitudinal folds in males, immaculate to light brown nuptial pads in males that cover the external part of the finger I, from the wrist to the second phalanx, and 11 pairs of chromosomes without heteromorphic sex chromosomes. From all other species of the genus it distinguishes by presenting very long hindlimbs, with tibio-tarsal articulation reaching beyond the end of the snout, and absence of T-shaped terminal phalanges. Tadpoles, advertisement call, and the karyotype are described as well.
Keywords: Amphibia; Pseudopaludicola; new species; tadpole; advertisement call; karyotype